2010
DOI: 10.1186/1471-2334-10-226
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of hepatitis B virus markers in a cohort of students in Bangui, Central African Republic

Abstract: BackgroundHepatitis B virus (HBV) is the major cause of chronic hepatitis, cirrhosis, and hepatocellular carcinoma. The global epidemiological scenario of HBV infection has been changing rapidly over the last two decades due to an effective immunization programme initiated by the World Health Organization. The objective of this study is to estimate the prevalence of HBV in apparently healthy young people and to identify the risk factors of transmission of the HBV among this population in Bangui.MethodsDried bl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
56
8
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(75 citation statements)
references
References 22 publications
4
56
8
1
Order By: Relevance
“…This differs from the declines in prevalence described worldwide, [28][29][30][31][32] as well as in the rural communities of Southeast Asia, 33 and even in the Amazon region. 34 Analysis of the prevalence of the marker of previous infection enables us to infer aspects of HBV distribution in the population studied.…”
Section: Discussioncontrasting
confidence: 48%
“…This differs from the declines in prevalence described worldwide, [28][29][30][31][32] as well as in the rural communities of Southeast Asia, 33 and even in the Amazon region. 34 Analysis of the prevalence of the marker of previous infection enables us to infer aspects of HBV distribution in the population studied.…”
Section: Discussioncontrasting
confidence: 48%
“…Other studies have reported that this high rate of infection with hepatitis B among youth could be attributed to riskysexual behaviors such as multiple sexual partners, tattoos and piercings, although the difference was marginally significant [17]. In our study, we did not collect data on tattoos and piercing to document an association with hepatitis B.…”
Section: Discussioncontrasting
confidence: 39%
“…However, it was observed that the higher the social class, the lower the number of children positive to HBsAg. This is similar to the findings in Bangui (Komas et al, 2010), and in Enugu (Emechebe et al, 2008). This could be because people in the upper socioeconomic class are less likely to patronize medical quacks, or indulge in activities that may promote infection with HBV such as alternative medicine.…”
Section: Discussionsupporting
confidence: 81%